DAMPAK KERJASAMA PERDAGANGAN INDONESIA-INDIA DALAM PRODUK DAGING KERBAU PADA TAHUN 2016-2018 - Idris, Muhammad; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study illustrates the impact of international cooperation between the governments of Indonesia and India in the Export of Buffalo Meat in 2016-2018. This study aims to analyze how Indonesia cooperates working with India, and is expected to be useful information.                        This research used qualitative methods carried out through literacy research.  In the research process, the information that had been obtained, then linked to the concept of international cooperation,  Liberalism's perspective, and the concept of Interdependency               The results of the research process are then presented as a description of the research. From this research, it is found that Indonesia imports Indian buffalo meat because India is the second largest meat exporter with exports to 65 countries and controls more than the world market share and has competitive meat prices. The high consumption of beef in Indonesia makes Indonesia annually import beef to cover the demand of beef in Indonesia. So that in 2016 the government determined that India as the country of the origin entry of boneless frozen buffalo meat into Indonesia. The background of beef import policy from India is merely done to increase supply in Indonesia, and people have more choices. Not only buffalo meat and innards, the government has also opened imports of frozen beef. Keywords: Indonesia, India, Import, Buffalo meat